Peningkatan Pelayanan Kelistrikan PT. PLN (Persero) Rayon Cakranegara untuk Meningkatkan Kepuasan Pelanggan - Lelia Anasthasia Makalmay , Gracia; Angelina Gani, Sylvia; Chika Delia Verninda, Ni Putu; Kinaya Eklesia, Wingka; Talidobel, Susilo (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Electricity plays a crucial role in supporting various aspects of human life, including lighting, public facilities, household needs, industry, and national economic growth. This community service activity was carried out at PT PLN (Persero) Rayon Cakranegara, Kota Mataram. The team was directly involved in supporting the implementation of electricity service programs through several activities such as socializing the 50% discount program, providing mobile service counters, distributing promotional brochures, collecting data on customers using new and old electric meters, updating asset data into the system, conducting operational workshops, and managing administrative customer service reports. These activities aimed to improve PLN service quality and customer satisfaction. The results showed that the team’s contributions helped expedite service processes, expand information dissemination to the public, improve customer data accuracy, and support administrative and operational efficiency within the company. Overall, this internship activity provided tangible benefits for both the internship team and PLN in enhancing the quality of electricity services.